THE IMPLEMENTATION OF THE QUALITY SYSTEM BASED ON HACCP PRINCIPLES FOR THE MANUFACTURE OF MEAT FROZEN SEMIFINISHED PRODUCTS - Guliya Agzamtdinovna Hamatgaleeva (Современная наука и инновации, 2022)
Implementation of quality system based on HACCP principles in the enterprise is a necessary step to ensure food safety or suitability for consumption. Proper preparation and implementation of quality systems based on HACCP principles is a complex task, solution of which allows to predict the occurrence and mitigate possible risks that may be caused by all sorts of problems related to food safety.